The Impact of Non-Financial Rewards on Organizational Attractiveness - K.E.P, Perera; R.A.I.C, Karunarathne (Asian Journal of Empirical Research, 2019)
The main objective of this study was to examine the impact of nonfinancial rewards on organizational attractiveness. Drawing on the social exchange theory we develop and empirically test a model to explain the role of nonfinancial rewards, i.e. work-life balance, learning opportunities, and career advancement on organizational attractiveness. Following the quantitative research approach we collected data from 88 undergraduate students from 3 main universities in management in Sri Lanka. To test the model we developed one hypothesis. The results of simple linear regression suggested that nonfinancial rewards had statistically significant effect on generation Y candidates’ organizational attractiveness. This study mainly contributes to enhancing our understanding of the social exchange theory.